1990
DOI: 10.1097/00000658-199001000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Recurrence of Hepatocellular Carcinoma

Abstract: Sixty-nine patients with hepatocellular carcinoma underwent curative hepatic resections as primary cases from 1981 to 1986. Seven patients died in the hospital after operation. The other 62 patients left the hospital and were closely followed for 25 to 78 months. Recurrence of carcinoma became obvious in 41 (66%) of 62 patients. The clinical and pathologic features of these 41 patients were not significantly different from those of the other patients. Recurrent tumors were found in the residual liver in 38 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
92
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(94 citation statements)
references
References 8 publications
1
92
0
1
Order By: Relevance
“…28,29 IM is thought to develop through tumor cell dissemination through the portal vein. 30 Previous studies using the mouse IM model indicate activation of RhoA 21 and AKT, 31 and overexpression of cortactin 32 Reduced TGFBR2 expression correlated with portal vain invasion in HCC cases, and poorly differentiated HCC cells showed lower TGFBR2 expression compared with well-differentiated cells.…”
Section: Tgfbr2 Expression In Hccsmentioning
confidence: 99%
“…28,29 IM is thought to develop through tumor cell dissemination through the portal vein. 30 Previous studies using the mouse IM model indicate activation of RhoA 21 and AKT, 31 and overexpression of cortactin 32 Reduced TGFBR2 expression correlated with portal vain invasion in HCC cases, and poorly differentiated HCC cells showed lower TGFBR2 expression compared with well-differentiated cells.…”
Section: Tgfbr2 Expression In Hccsmentioning
confidence: 99%
“…Prognosis of HCC is extremely poor with a 5-year survival rate of less than 5% for late primary HCC (Block et al, 2003). The poor prognosis of HCC patients is mainly attributed to the high rate of intrahepatic metastasis after treatment (Nagao et al, 1990). Despite the advances in molecular technologies, which allow the identification of novel targets involved in HCC metastasis, the precise mechanisms involved remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, prognosis after hepatectomy is still unsatisfactory because of a high incidence of disease recurrence. 1,2 Pathologic and genetic studies have identified two types of recurrence of HCC, i.e., intrahepatic metastasis of the primary HCC and multicentric development of new tumors, although the two types cannot always be distinguished. It is generally believed that disease recurrence due to intrahepatic metastasis is likely to appear soon after surgical resection and that its risk decreases with prolongation of the postoperative period.…”
mentioning
confidence: 99%